Belgian Wildlife as Potential Zoonotic Reservoir of Hepatitis E Virus. Issue 3 (31st October 2015) - Thiry, D.; Mauroy, A.; Saegerman, C.; Licoppe, A.; Fett, T.; Thomas, I.; Brochier, B.; Thiry, E.; Linden, A.
Summary: Hepatitis E is an acute human liver disease in healthy individuals but may become chronic in immunocompromised patients. It is caused by the hepatitis E virus (HEV) and can have a zoonotic origin, particularly in high‐income countries. In this study, 383 sera from wild boars were selected for serology; for virological analyses, 69 sera and 61 livers from young wild boars were used. A total of 189 and 235 sera of, respectively, red deer and roe deer were collected for serological analysis. For virological analyses, 84 and 68 sera and 29 and 27 livers from, respectively, red and roe deer were sampled. An apparent seroprevalence of 34% (95% CI 29.71–39.46) was found in wild boars, of 1% (95% CI 0–2.4) in red deer and 3% (95% CI 0.8–4.2) in roe deer. To assess the ELISA screening prevalence, Western blot (WB) analyses were carried out, a receiver operating characteristic curve analysis was performed and different scenarios with varying ELISA specificities relative to WB were analysed. Seroprevalence remained high whatever the scenario in the wild boar population. In wild boar, 4 of 69 sera and 4 of 61 livers were detected as positive for HEV RNA. All sequences obtained from sera belonged to genotype HEV‐3. HEV RNA, belonging to genotype HEV‐3, was detected in one of 29 red deer livers. Wild boar can be considered as a host reservoir of the virus in Belgium. However, in contrast to the epidemiological role played by them in other countries, the low prevalence in deer makes these species an unlikely reservoir. This evidence needs further investigation to determine in which situation deer can serve as reservoir. These results also raise the question of the dynamics of HEV infection between wild fauna, domestic pigs and humans.